Exogenous l-Valine Promotes Phagocytosis to Kill Multidrug-Resistant Bacterial Pathogens - Chen, Xin-hai (Front Immunol, 2017)
The emergence of multidrug-resistant bacteria presents a severe threat to public health and causes extensive losses in livestock husbandry and aquaculture. Effective strategies to control such infections are in high demand. Enhancing host immunity is an ideal strategy with fewer side effects than antibiotics. To explore metabolite candidates, we applied a metabolomics approach to investigate the metabolic profiles of mice after Klebsiella pneumoniae infection. Compared with the mice that died from K. pneumoniae infection, mice that survived the infection displayed elevated levels of l-valine. Our analysis showed that l-valine increased macrophage phagocytosis, thereby reducing the load of pathogens; this effect was not only limited to K. pneumoniae but also included Escherichia coli clinical isolates in infected tissues. Two mechanisms are involved in this process: l-valine activating the PI3K/Akt1 pathway and promoting NO production through the inhibition of arginase activity. The NO precursor l-arginine is necessary for l-valine-stimulated macrophage phagocytosis. The valine-arginine combination therapy effectively killed K. pneumoniae and exerted similar effects in other Gram-negative (E. coli and Pseudomonas aeruginosa) and Gram-positive (Staphylococcus aureus) bacteria. Our study extends the role of metabolism in innate immunity and develops the possibility of employing the metabolic modulator-mediated innate immunity as a therapy for bacterial infections.